Evaluasi Kinerja dan Biaya Pengangkutan Batubara Menggunakan Dump Truck dan Belt Conveyor pada Penambangan Muara Tiga Besar Utara PT. Bukit Asam, Tbk. - Muhammad Fuadi Shiddiqi; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Based on observations in the field in the process of transporting coal from the mining front to the temporary stockpile at the Coal Mine Muara Tiga Besar Utara PT. Bukit Asam, Tbk, obtained transportation equipment productivity is not optimal. This is because there is a long queue of dump trucks in the dumping process of coal material to the dump hopper, as well as low work efficiency of the tool. Actual productivity of dump trucks from field observations is 36.77 tons / hour on fleet 1 and 52,64 tons / hour on fleet 2, while productivity of conveyor belts is 1640,21 tons / hour. After the analysis is obtained the cause of the low productivity of the tool is low work efficiency. By increasing work efficiency, the ideal productivity of dump trucks is 50.72 tons / hour on fleet 1 and 72.60 tons / hour on fleet 2, while the ideal productivity of conveyor belts is 1879.41 tons / hour. From the calculations, the cost of transporting coal from the mining front to the temporary stockpile using a dump truck is Rp.17.882 / ton, using a dump truck and a conveyor belt is Rp.23.631 / ton. After an analysis of the amount of the cost of transporting coal using a dump truck is Rp. 14,576 / ton, using a dump truck and conveyor belt is Rp.17,705 / ton.Keywords: Front, Temporary Stockpile, Productivity, Work Efficiency, Fleet, Cost Transportation